Comparative ruralism and 'opening new windows' on gentrification. Issue 1 (March 2018) - Phillips, Martin; Smith, Darren P
In response to the five commentaries on our paper 'Comparative approaches to gentrification: lessons from the rural', we open up more 'windows' on rural gentrification and its urban counterpart. First, we highlight the issues of metrocentricity and urbanormativity within gentrification studies, highlighting their employment by our commentators. Second, we consider the issue of displacement and its operation within rural space, as well as gentrification as a coping strategy for neoliberal existence and connections to more-than-human natures. Finally, we consider questions of scale, highlighting the need to avoid naturalistic conceptions of scale and arguing that attention could be paid to the role of material practices, symbolizations and lived experiences in producing scaled geographies of rural and urban gentrification.